The linguistic and construct validity of the Malay version of the Coping Self-Efficacy Scale (CSES-My): Evidence from a sample of Malaysian parents of children with leukemia or lymphoma - Tan, Chai-Eng; Tan, Kit-Aun; Lau, Sie Chong Doris; Teh, Kok Hoi; Sidik, Sherina Mohd (Belitung Nursing Journal, 2024)
Background: Parents of children with hematological cancers such as leukemia and lymphoma need to cope with stress related to their child’s diagnosis. The Coping Self-Efficacy Scale is a widely used and validated tool to measure an individual’s confidence in dealing with stressful situations. Appropriate translation and validation are needed to produce a localized language version suitable for Malaysian contexts. Objective: The study aimed to examine the linguistic and construct validity of the Malay version of the Coping Self-Efficacy Scale (CSES-My) among parents of children with hematological cancer. Methods: The CSES-My was created through a sequential series of steps, starting with the translation of the original English version, followed by cultural adaptation, and then cognitive interviewing. The 26-item CSES-My was self-administered in a sample of parents of children with leukemia and lymphoma from October 2021 until February 2022. They were recruited via online or face-to-face methods. Exploratory factor analysis was performed to examine the construct validity of the CSES-My. Results: A total of 165 complete responses were analyzed. The scale has two factors, including Personal Coping and Social Coping, accounting for 58.3% of the variance. Personal Coping (19 items, Cronbach’s alpha = 0.958) represented the respondents’ self-efficacy for independently executing coping strategies, whether through solving problems or changing the way they think about the situation. Social Coping (6 items, Cronbach’s alpha = 0.867) represented their confidence in executing coping strategies, which involved using social resources such as seeking external support, distraction, and avoiding loneliness. Conclusions: The CSES-My had reliable and valid psychometric properties, providing evidence for its utility in evaluating coping self-efficacy among parents of children with leukemia or lymphoma in Malaysia. The CSES-My is a valuable tool for nurses and other healthcare professionals investigating coping self-efficacy in Malay-speaking populations, and it may also aid in the development of future coping interventions.